PELAKSANAAN PEMBELAJARAN DI PESANTREN MA’AHAD AZZEIN AL-MAKKY KELURAHAN WEK VI KECAMATAN PADANGSIDIMPUAN SELATAN KOTA PADANGSIDIMPUAN SUMATERA UTARA - Hasibuan, Asnita; Maemunaty, Titi; Widiastuti, Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
The aim of this study is to discover the learning implementation in the Ma'ahad Azzein AL-Makky Islamic boarding school in the Wek VI subdistrict, South Padangsidimpuan, Padangsidimpuan, North Sumatra. This study uses a descriptive method with a qualitative approach, which aims to discover the learning implementation in the Ma'ahad Azzein AL-Makky Islamic boarding school in Wek VI, South Padangsidimpuan district, Padangsidimpuan City, North Sumatra. This study consists of one variable, namely the implementation of learning with 3 indicators, 6 sub-indicators and 20 dimensions, namely the first indicator of Input (input element), 1. Student or santri sub-indicators, a) Gender dimensions, b) Age dimensions, c) Physical maturity, d) Spiritual maturity. 2. Instrument factor Sub-indicator, a) Educator or Ustadh, b) curriculum or curriculum, c) learning materials and teaching materials, d) learning methods, e) learning facilities and infrastructure, f) learning time, g) learning evaluation. 3) Environmental indicator Sub-indicators, a) Physical factors, b) Social factors, c) Psychological factors. 4) Knowledge sub-indicator, a) Explain, b) Apply. 5) Attitude Indicator Sub, a) Accept, b) Refuse. 6) Skill indicator Sub, a) Al-Quran recitation, b) Al-Quran reading ability. Data collection techniques can be performed through observations, interviews and documentation. The results of this study The process of implementing learning in the Islamic boarding school Ma'ahad Azzein Al-Makky went well, in terms of educators, learning materials, learning methods, learning time and learning evaluation. But there are still people who are not suitable, for example, they do not use the curriculum in the pesantren, because the main program is only the Tahfizh of the Quran and the infrastructure is still missing.Key Words: Implementation, Learning